PREEKLAMPSIA SEBAGAI SALAH SATU FAKTOR RISIKO TERHADAP KERUSAKAN FUNGSI SEL RAMBUT LUAR KOKLEA - , Oppy Surya Atmaja ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Preeclampsia is one of the most common complications of pregnancy in the world. In Indonesia, the insidence of preeclampsia lies between 3-10% of all pregnancies each year and according to medical data recorded at RSUP Sardjito Yogyakarta, total cases of preeclampsia between the year of 2009-2011 are 277 cases. Preeclampsia is a multisystem disorder which causes endothelial dysfunction and vasospasm that may leads to ischaemia and organ damage especially those of end organs. Cochlea serves as an end organ which makes it vulnerable to damage under ischaemic condition. Objective: This research was aimed to understand the role of preeclampsia on cochlear outer hair cells dysfunction. Methods: Research design used was cross sectional study. Subjects of the research were pregnant women who were hospitalized in Obstetry and Gynecology ward of RSUP Dr. Sardjito, Yogyakarta who were qualified for the inclusion and exclusion criteria. Diagnosis of preeclampsia was obtained by hypertensive blood pressure measurement and the evidence of proteinuria by dipstick method. Meanwhile, cochlear outer hair cells function was measured by the distortion otoaccoustic emission method. Statistical analysis for this research employed chi square test, logistic regression, independent sample ttest. Result: Based on the results of the distortion otoaccoustic emission test, REFER resulted in 6 people in the preeclamptic group (10%) and none in the group non-preeclampsia whom had a REFER result of p = 0.027 with a prevalence ratio of 7 (95% CI 0.89 to 55, 23). Conclusion: This result demonstrated that preeclampsia is proven to be one of the risk factors for the destruction of cochlear outer hair cell function.